Business ethics - ten Bos, René (Henry Stewart Talks, 2010)
Business ethics, Oxymoronic language, Philosophical ethics, Utilitarianism, Deontology, Virtue ethics, Ethics and reason, Reason as calculation, Reason as universalism, Reason as talking, Corporate codes as an instance of reasonable ethics, Criticism of business ethics, Ethics and emotion, Ethics and embodiment